2015
DOI: 10.5507/bp.2014.036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Helicobacter pylori eradication on insulin resistance and HbA1c level in people with normal glucose levels: a prospective study

Abstract: Background and Aim. Helicobacter pylori (H. pylori) infection is reported to be associated with various extragastrointestinal conditions such as insulin resistance, diabetes mellitus and metabolic syndrome. These conditions are attributed to systemic inflammation, leptin or ghrelin changes due to H. pylori infection. Therefore, increasing trends in the management of H. pylori infection are ordered to maintain glycemic control. In this study, we evaluated the effect of H. pylori eradication on insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
(27 reference statements)
3
27
2
2
Order By: Relevance
“…Also, significant difference of FPI and HOMA-B (as an insulin secretion index) between the treatment group and placebo group confirmed increasing insulin resistance of the treatment group. In fact, in contrast to other studies,[232429303132333435] HP eradication with antibiotics did not improve insulin resistance but increased it.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Also, significant difference of FPI and HOMA-B (as an insulin secretion index) between the treatment group and placebo group confirmed increasing insulin resistance of the treatment group. In fact, in contrast to other studies,[232429303132333435] HP eradication with antibiotics did not improve insulin resistance but increased it.…”
Section: Discussioncontrasting
confidence: 96%
“…There are several studies, which confirmed the relationship between HP infection and insulin resistance. [232429303132333435] Among them, some researches specifically studied the effect of HP eradication on insulin resistance. In a study by Dogan et al .,[30] 370 patients with HP infection were chosen and treated for HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies also demonstrated the causal relationship between H. pylori and IR (Polyzos et al, 2013b; Chen et al, 2015). A prospective study reported that after H. pylori eradication, the fasting plasma insulin level ( p < 0.01) and HOMA-IR ( p < 0.01) were significantly lower than before treatment, indicating that H. pylori eradication improved IR and may prevent the occurrence of MS, and NAFLD (Abenavoli et al, 2013; Dogan et al, 2015). …”
Section: The Possible Mechanisms Of the Influence Of H Pylori Infectmentioning
confidence: 99%
“…We all know that H. pylori infection is one of the most important environmental risk factors for the diseases of chronic gastritis, peptic ulcers, gastric mucosa-associated lymphoid tissue (MALT) lymphoma, and gastric cancer. Recently, accumulating evidence implicates H. pylori infection existing in the patients with extragastrointestinal diseases, including idiopathic thrombocytopenic purpura, ischemic heart diseases, obesity, type 2 diabetes mellitus (T2DM) (Wong et al, 2014; Dogan et al, 2015; Nasif et al, 2016). In addition, there is a special focus on the relationship between H. pylori infection and NAFLD.…”
Section: Introductionmentioning
confidence: 99%